Trade negotiations in agriculture : a future common agenda for Brazil and Canada? - Gaisford, James D. (James Donald), 1955-; Kerr, William A. (William Alexander) (Turning points : occasional papers in Latin American studies series, 2005)
This first book in the new series 'Turning Points: Latin American Studies Occasional Papers' (a joint venture between the Latin American Research Centre and the University of Calgary Press) is the result of a conference immediately following the Cancun World Trade Organisation (WTO) Ministerial meeting attended by prominent scholars and activists. The main objective of the conference was to distil issues on which Canada and Brazil could work together on common strategic interests to build a coalition and benefit from cooperation. The book examines topics such as the roles of Brazil and Canada in the WTO and the Free Trade Area of the Americas (FTAA) and considers each country's position on specific trading issues. This book is a valuable resource for anyone engaged in or teaching contemporary trade negotiations.